Hormonal regulation of AMPA receptor trafficking and memory formation - Krugers, Harmen J.; Hoogenraad, Casper (Frontiers in Synaptic Neuroscience, 2009)
Humans and rodents retain memories for stressful events very well. The facilitated retention of these memories is normally very useful. However, in susceptible individuals a variety of pathological conditions may develop in which memories related to stressful events remain inappropriately present, such as in post-traumatic stress disorder. The memory enhancing effects of stress are mediated by hormones, such as norepinephrine and glucocorticoids which are released during stressful experiences. Here we review recently identified molecular mechanisms that underlie the effects of stress hormones on synaptic efficacy and learning and memory. We discuss AMPA receptors as major target for stress hormones and describe a model in which norepinephrine and glucocorticoids are able to strengthen and prolong different phases of stressful memories.